Prediction of aquaporin function by integrating evolutionary and functional analyses - Perez Di Giorgio, Juliana Andrea; Soto, Gabriela Cinthia; Alleva, Karina Edith; Jozefkowicz, Cintia; Amodeo, Gabriela; Muschietti, Jorge Prometeo; Ayub, Nicolás Daniel (Springer, 2019)
Aquaporins (AQPs) are a family of channel proteins, which transport water and/or small solutes across cell membranes. AQPs are present in Bacteria, Eukarya, and Archaea. The classical AQP evolution paradigm explains the inconsistent phylogenetic trees by multiple transfer events and emphasizes that the assignment of orthologous AQPs is not possible, making it difficult to integrate functional information. Recently, a novel phylogenetic framework of eukaryotic AQP evolution showed congruence between eukaryotic AQPs and organismal trees identifying 32 orthologous clusters in plants and animals (Soto et al. Gene 503:165–176, 2012). In this article, we discuss in depth the methodological strength, the ability to predict functionality and the AQP community perception about the different paradigms of AQP evolution. Moreover, we show an updated review of AQPs transport functions in association with phylogenetic analyses. Finally, we discuss the possible effect of AQP data integration in the understanding of water and solute transport in eukaryotic cells.